Healthcare Systems Design At a Crossroads: Challenges, Opportunities and Strategies. (September 2013) - Perry, Shawna J.; Mosher, Hilary J.; Persoon, Thomas J.; Bass, Ellen J.; Fairbanks, Rollin (Terry) J.; Pennathur, Priyadarshini R.
The healthcare work system contains many constraints resulting from changes in workflow and system structure. The panel reflects on challenges in the healthcare work system human factors researchers can address to improve patient safety. The panelists address: (1) the growing complexities in healthcare and patient safety from the provider and patient perspectives; (2) successful applications of human factors approaches to healthcare systems design; (3) and barriers in following a systems approach and strategies to overcome the challenges that remain for enhancing patient safety.